Solid Platelet Rich Plasma in Corneal Surgery. Issue 1 (June 2016) - Arnalich, Francisco; Rodriguez, Alejandra; Luque-Rio, Alvaro; Alio, Jorge
Abstract Abstract Solid eye platelet-rich plasma (E-PRP) concentrates platelets in a small volume of plasma which contains a high concentration of important growth factors and cell adhesion molecules. These cell adhesion molecules and growth factors occupy a major role in wound healing and enhance the physiological procedure at the site of the injury or the surgery. There are different materials used to tectonically maintain the solid clot attached at the site where treatment is necessary. Although AM may be used for this purpose, other biomaterials such a bovine pericardium or autologous fibrin membrane are at least as effective with less interdonor variations, no biological hazards, providing a better surgical alternative than the biologically so variable amniotic membrane patch. Solid platelet-rich plasma in the form obtained in ophthalmology, E-PRP, is a reliable and effective surgical coadjuvant to promote corneal wound healing in severe corneal ulcers and corneal perforations, and may be associated with other ocular surface reconstruction procedures. Funding Supported in part by a grant from the Spanish Ministry of Science and Innovation, Centro para el Desarrollo Tecnológico Industrial (CDTI), CENIT: "Customized Eye Care", CeyeC (CEN-20091021).